Towards inclusivity in (English-Spanish) scientific translation of person’s names without breaking the rules - Vázquez y del Árbol, Esther (Lenguas Modernas, 2025)
English language, the lingua franca for science, is a genderless language that must be daily rendered into Spanish language, a gendered language. Considering the need for further inclusion, we present this research paper, focused on the English-Spanish translation of a corpus of scientific items, by selecting 4 reputed English scientific journals representative of the latest advances in the area of Science. Then, we selected 15 scientific English genderless names related to people, that could be challenging since they must be rendered into a gendered language (Spanish). Subsequently, we performed a lexicographic research by searching every terminological item within monolingual scientific dictionaries, bilingual (English-Spanish) scientific dictionaries, and bilingual (non-specialized) dictionaries. Our research outcomes unveil how the researched references did not offer a significant number of genderless translations, whilst our translation proposals illustrated how Spanish language may resort to interesting different translation options for rendering an inclusive Spanish, without breaking grammatical rules.